Obstructive sleep apnea in adults with type 1 and type 2 diabetes: perspectives from a quality improvement initiative in a university-based diabetes center - Ioja, Simona (BMJ Open Diabetes Res Care, 2017)
OBJECTIVE: Obstructive sleep apnea (OSA) and diabetes are frequent comorbid conditions. Screening for OSA in patients with diabetes is recommended but the frequency with which this is done in clinical practice is unknown. The objectives of this quality improvement initiative were to identify clinician and patient perceptions regarding OSA and to identify the prevalence of patients at high risk for OSA (HROSA). METHODS: A quality improvement initiative was conducted to query clinicians and patients attending a specialty diabetes clinic regarding attitudes and beliefs related to OSA. The Berlin Questionnaire was embedded in patient questionnaires to identify patients as low risk for OSA (LROSA) or HROSA. RESULTS: 35 clinicians completed questionnaires with >80% agreement that OSA contributed to blood pressure (BP), glycemic control, and diabetes complications and that screening is a shared responsibility with other physicians; but only 17% indicated regular screening due predominantly to insufficient time. Of 107 patients (26 type 1 diabetes mellitus (T1DM) and 81 type 2 diabetes mellitus (T2DM)), 30% were aware that OSA could affect diabetes outcomes. The prevalence of known OSA, LROSA, and HROSA was similar in T1DM (15%, 50%, 35%) and T2DM (36%, 33%, 31%, respectively) (p=0.21). 59% of all HROSA patients indicated that OSA screening had never been discussed with them. CONCLUSIONS: These results demonstrate that providers, but not patients, are knowledgeable about the importance of OSA screening, but insufficient time is a major barrier to wider screening. Approximately, 30% of patients with T1DM and T2DM were identified as HROSA supporting the need for procedures that improve detection and treatment.